PENGARUH PENGENDALIAN INTERNAL, SISTEM INFORMASI AKUNTANSI, MOTIVASI KERJA DAN KAPASITAS SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN - Friska Septriyanda Patraini; Fajar Gustiawaty Dewi; Dewi Sukmasari (Faculty of Economics and Business, 2021)
Layoffs carried out by construction companies are caused by the weak performance of employees working at the company. Apart from being based on labor issues, layoffs are also influenced by internal problems in construction service companies. Given this phenomenon, it is necessary to conduct research on the performance of construction company employees. In order to improve employee performance, internal control is needed that can reduce the occurrence of actions that are not in accordance with the rules. Where good internal control is shown by an efficient and effective accounting information system, especially in presenting information in accordance with the needs of management and other parties who need it. In addition, employee performance can also decrease, this is due to a decrease in work motivation in employees. Work motivation is also related to the capacity of human resources, so that employee performance must be supported by the capacity of competent human resources to provide optimal benefits.